Gearbreakers - Mikuta, Zoe Hana, 2000- (Square Fish, 2022)
In an age of 100-foot-tall mechanical deities run by a tyrannical regime, two teenaged girls on opposite sides of a war discover they are fighting for a common purpose--and falling for each other.